2017
DOI: 10.3390/w9010043
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Fish Removal to Restore Lakes: Case Study of Lake Væng, Denmark—Two Biomanipulations during 30 Years of Monitoring

Abstract: Biomanipulation by fish removal has been used in many shallow lakes as a method to improve lake water quality. Here, we present and analyse 30 years of chemical and biological data from the shallow and 16 ha large Lake Vaeng, Denmark, which has been biomanipulated twice with a 20-year interval by removing roach (Rutilus rutilus) and bream (Abramis brama). After both biomanipulations, Lake Vaeng shifted from a turbid, phytoplankton-dominated state to a clear, water macrophyte-dominated state. Chlorophyll a was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 60 publications
0
30
1
Order By: Relevance
“…Repeated treatment has therefore been suggested [7]. In an article in this special issue [21], an analysis is presented of 30 years of chemical and biological data on shallow 16 ha Danish Lake Vaeng that has been biomanipulated twice with a 20-year interval by removing coarse fish, the second time due to unsatisfactory long-term results. After both biomanipulations, the lake shifted from a turbid, phytoplankton-dominated state to a clear water macrophyte-dominated state.…”
Section: Temperate Climate Zonementioning
confidence: 99%
“…Repeated treatment has therefore been suggested [7]. In an article in this special issue [21], an analysis is presented of 30 years of chemical and biological data on shallow 16 ha Danish Lake Vaeng that has been biomanipulated twice with a 20-year interval by removing coarse fish, the second time due to unsatisfactory long-term results. After both biomanipulations, the lake shifted from a turbid, phytoplankton-dominated state to a clear water macrophyte-dominated state.…”
Section: Temperate Climate Zonementioning
confidence: 99%
“…Monthly averages of Small (left 3 panels) and Large (right 3 panels) organisms of Diaphanosoma (upper 2 panels), Bosmina (middle 2 panels) and Ceriodaphnia (2 lower panels) densities (No./l) in Lake Kinneret (1975Kinneret ( -1985. The fish removal by fishery management was documented by Sondergaard et al [22]. This kind of management, namely, Biomanipulation, has been used in many shallow lakes aimed at water quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This provides further evidence [3] of the usefulness of biomanipulation as a restoration technique in warm shallow eutrophic lakes after a sufficiently high external loading reduction. However, in temperate lakes, repeated fish removal is suggested to obtain a longer-lasting clear water state [3,50], and such repeated removal may also be recommended for warm shallow lakes. The warm lakes are dominated by omnivorous fish in both the turbid and the clear water states [32], and it has been shown that adult omnivores feed mainly on submerged macrophytes in the restored part of Huizhou West Lake [37] as well as in Lake Wuli [38], and high abundances of these species could lead to a return of the turbid state.…”
Section: Discussionmentioning
confidence: 99%